PENYUSUNAN PROGRAM APLIKASI ADMINISTRASI PENELITIAN PADA LEMBAGA PENELITIAN UNIVERSITAS XYZ - Sugondo, Verdiana (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Research is an opportunity for teachers to develop their knowledge. reseach group XYZ University is an institute for XYZ University’s teaching staff to submit their research paper. Curriently, research administration process in reseach group XYZ University is done manually. Thus the process is inefficient. Research administration application program in reseach group XYZ University is a website based program used to help during the implementation process. The purposes of this application program are to help administrator in writing and searching letters, writing report, and organizing schedules. For reviewer, program is useful to asses the research. The program can support the researcher to register their research. Based on user, there is in this application program, for researcher, reviewer, admininistrator, researcher and reviewer. The application program employs SDLC (System Development Life Cycle) method, consist of planning, analysing, designing, implementation. The result of this program can enhance the performance in research group administrator in Tarumanagara University.